1998
DOI: 10.1037/0882-7974.13.3.462
|View full text |Cite
|
Sign up to set email alerts
|

Identification of speeded and slowed familiar melodies by younger, middle-aged, and older musicians and nonmusicians.

Abstract: There is a range of tempos within which listeners can identify familiar tunes (around 0.8 to 6.0 notes/s). Faster and slower tunes are difficult to identify. The authors assessed fast and slow melodyidentification thresholds for 80 listeners ages 17-79 years with expertise varying from musically untrained to professional. On fast-to-slow (FS) trials the tune started at a very fast tempo and slowed until the listener identified it. Slow-to-fast (SF) trials started slow and accelerated. Tunes either retained the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
6
31
0
Order By: Relevance
“…Of particular interest here is that the reduction in range for older participants was mostly in the fast end of the spectrum. This finding agrees with that of Andrews et al (1998), in that the identification threshold for fast melodies shifted with age, but the identification threshold for slow melodies did not.…”
supporting
confidence: 82%
See 4 more Smart Citations
“…Of particular interest here is that the reduction in range for older participants was mostly in the fast end of the spectrum. This finding agrees with that of Andrews et al (1998), in that the identification threshold for fast melodies shifted with age, but the identification threshold for slow melodies did not.…”
supporting
confidence: 82%
“…At very slow rates, earlier elements are likely to be lost from WM by the time later elements are processed, making access to the entire sequence difficult. However, Andrews et al (1998) found no such effect. Therefore, the cognitive slowing hypothesis appears to provide a better explanation of our earlier results than do the general effects of a WM deficit.…”
mentioning
confidence: 75%
See 3 more Smart Citations